University Aston looking into prospects of collaboration with UMP - Wan Nazrul Helmy, Wan Mohd Zain
Universiti Malaysia Pahang (UMP)’s post-graduate programme in technology and engineering was among the prospects which Aston University from UK was looking into before cooperating with UMP.